Elementy gospodarki funduszowej w systemie budżetowym rad narodowych - Wierzbicki, Janusz (Wydział Prawa i Administracji UAM, 1966)
The regional special purpose funds came into existence in the so called autonomous period of national councils, after the year of 1956. The existence of said funds seems to be advisable, despite the fact that they are incompatible with the principle of the unity of the state's budget, as they make possible to finance some projects outside the rather rigorous scope of the budget economy. They also permit to economize the budget funds and to reduce the size of the central budget's dotations. A similar character has the special accumulation of the budget funds, f. ex. in the form of additional payments of the population, the state's and cooperatives enterprises with a view of financing the communal facilities. The various elements of the funds economy, in the system of regional budgets are further linked with a possibility of using the budget surpluses from past years. This ought to be an incentive for a better, namely more careful spending of the budget funds. However, there are some restrictions in the policies of spending the said surpluses, which run contrary to the above mentioned incentives. The entirely free way of using the surpluses which originate from not fully drawn upon investment funds — should, however, be limited. A new feature of the regional budget economy is the project to set up — from parts of the surpluses — the so called equation funds, destined to cover the deficits. The idea of those funds seems to be justified, there are, on the other hand, some doubts on how those funds ought to be administered.